Dual effectiveness of ascorbic acid and ethanol combined treatment to inhibit browning and inactivate pathogens on fresh-cut apples. (July 2017) - Yan, Shoulei; Luo, Yaguang; Zhou, Bin; Ingram, David T.
Abstract: Fresh-cut apples have recently been associated with several recalls due to food-borne pathogen contamination. Simultaneous control of enzymatic browning and pathogen growth is challenging, because of the incompatibility between most chemicals applied for these two purposes. This study evaluated the efficacy of ethanol in combination with ascorbic acid to inhibit browning and inactivate pathogens on apple slices. Apple slices were dipped in solutions containing 10%–40% (v/v) ethanol (E) and 1% (m/v) ascorbic acid (AA), dewatered, packaged, and stored at 1.5 °C. In parallel experiments, apple slices were dip-inoculated with Escherichia coli ( E. coli ) O157:H7 and Listeria monocytogenes ( L. monocytogenes ) prior to treatment. Treatments with 20–40% E significantly inhibited the growth of aerobic bacteria, and yeast and mold during storage. Treatment with 20% E plus 1% AA maintained the lightest flesh color and highest tissue firmness. Meanwhile, treatment with 30% E plus 1% AA led to highest microbial inactivation, together with effective browning inhibition and firmness maintenance. Furthermore, 30% E plus 3% AA reduced pathogen populations immediately after treatment and further during cold storage, demonstrating that this combined treatment can enhance safety, as well as quality of fresh-cut apples. Highlights: Ethanol 20–40% plus 1% ascorbic acid inhibited microbial growth on apple slices. Ethanol 20–30% plus 1% ascorbic acid prevented browning and softening of apple slices. Ethanol 30% plus 3% ascorbic acid inhibits L. monocytogenes growth on apple slices. Ethanol 30% plus 3% ascorbic acid inhibits E. coli O157:H7 growth on apple slices.